A Fresh Look at Drainage for Agriculture†. (23rd July 2018) - Parsinejad, Masoud; Akram, Mojtaba
Abstract: Historically, drainage systems have been considered as tools for removing excess water. In the past two decades, however, a more comprehensive and inclusive approach has been developed that considers drainage as only one of the central elements of an integrated and comprehensive water management scheme. Since its invention, the science and technology of agricultural drainage have undergone development in the formulation of design, materials and methods. Recently, more concern has been focused on the environmental consequences of adoption of drainage systems. Now, environmental conservation is the greatest challenge for drainage globally. The 13th International ICID Drainage Workshop, held from 4 to 7 March 2017 in Ahwaz City, Iran, was entitled Drainage and Environmental Sustainability, to address these challenges. Of the presentations, a number focused on the new outlook and technologies that have recently been adopted. In this paper, these presentations have been used to provide a brief history of the invention and development of materials and methods in agricultural drainage. Under the notion of 'beyond modern drainage', the latest innovations in materials and management of agricultural water, in general, and drainage systems in particular, are presented. © 2018 John Wiley & Sons, Ltd.